Analysis of the Implementation of Mudharabah and Musyarakah Contracts, Transparency, and Member Empowerment in Islamic Cooperatives - M. Iqbal Tawakkal; Wargo; Ahmad Dahlan Salleh (Zabags International Journal of Islamic Studies, 2025)
Islamic cooperatives have emerged as alternative microfinance institutions expected to meet the public’s demand for a fair, transparent, and Sharia-compliant financing system. However, in practice, the implementation of profit-sharing contracts such as mudharabah and musyarakah still faces various challenges, particularly in terms of member comprehension, profit distribution mechanisms, and the effectiveness of cooperative education programs. This study aims to analyze the application of Sharia contracts in microenterprise financing by Islamic cooperatives and to evaluate members’ perceptions and experiences of the system. Employing a qualitative approach with a case study strategy, data were collected through in-depth interviews, direct observation, and document analysis from Islamic cooperatives actively financing micro-entrepreneurs. The findings reveal that members’ understanding of Sharia contracts remains limited, transparency in profit-sharing is suboptimal, and cooperative training programs have not reached all members equitably. Although cooperative financing has positively impacted members’ business development, such success is not yet fully supported by operational systems aligned with Sharia values. This study contributes conceptually to strengthening community-based Islamic economic theory and offers practical recommendations for cooperative managers and policymakers in designing more equitable, participatory, and sustainable financing systems.